2013
DOI: 10.1371/journal.pone.0080813
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Artificial Selection on Runs of Homozygosity in U.S. Holstein Cattle

Abstract: The intensive selection programs for milk made possible by mass artificial insemination increased the similarity among the genomes of North American (NA) Holsteins tremendously since the 1960s. This migration of elite alleles has caused certain regions of the genome to have runs of homozygosity (ROH) occasionally spanning millions of continuous base pairs at a specific locus. In this study, genome signatures of artificial selection in NA Holsteins born between 1953 and 2008 were identified by comparing changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
207
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(234 citation statements)
references
References 39 publications
22
207
3
2
Order By: Relevance
“…The maximum size of ROH was 112.65 Mb and was found on BTA8 in Cinisara breed. Kim et al (2013) . The comparison of ROH is not straightforward since different studies used different criteria in particular for the minimum length of ROH and the minimum number of SNPs involved in ROH.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum size of ROH was 112.65 Mb and was found on BTA8 in Cinisara breed. Kim et al (2013) . The comparison of ROH is not straightforward since different studies used different criteria in particular for the minimum length of ROH and the minimum number of SNPs involved in ROH.…”
Section: Resultsmentioning
confidence: 99%
“…Although the frequency and genomic distribution of ROH has been characterized in humans (McQuillan et al 2008(McQuillan et al , 2012Auton et al 2009;Nalls et al 2009;Kirin et al 2010;Nothnagel et al 2010;Polašek et al 2010;Pemberton et al 2012) and commercial livestock or closely related species (Pollinger et al 2011;Purfield et al 2012;Ferenčaković et al 2013;Kim et al 2013;MacLeod et al 2013), we know little about ROH in natural populations of nonmodel organisms where demographic histories and genomic characteristics often differ substantially from humans and livestock. The rapidly increasing availability of genome assemblies and resequencing data in nonmodel organisms now makes it possible to study ROH at a very high resolution in any species.…”
mentioning
confidence: 99%
“…The changes in genetic aspects of behavioural control for new adaptations, from survive to thrive, and using available resources have also been detected under positive selection in several populations (Randhawa et al, 2016). Kim et al (2013) found that several of the regions that had differing levels of ROH across populations were associated with economically important traits including milk, fat and protein yield. The same approach was utilized in this study to detect signatures of selection in common and different across populations.…”
Section: Resultsmentioning
confidence: 99%
“…Due to this the usefulness of F ST to determine regions that are different within a breed is reduced, therefore alternative methods have been used (Howard et al, 2015). One such alternative method to characterize the genomic differences across populations is to compute the average or a specific region's ROH (runs of homozygosity) frequency (Ferenčaković et al, 2013;Kim et al, 2013).…”
Section: Introductionmentioning
confidence: 99%